Hydraulic organization and the vulnerable livestock migration in the Ferlo zone (Sénégal) - Sy, Oumar (Sustainability in Debate, 2010)
One of the major characteristics of the Ferlo zone is the rainfall vagary which affects negatively the correct filling of ponds and increases the vulnerability of pastoral societies. The pastoral hydraulic policies, in terms of bad management of drillings made it possible to develop only extensive livestock farming. In the same way, the policies of control of surface water contributed to the marginalization of the livestock farming in the Senegal river’s alluvial valley. In this context, the State created some ponds in order to mobilize and develop surface waters for the purpose of reducing climate constraints. This study shows that constraints on access, conservation and management of water resources constitute a major challenge to the development of the Senegalese Sahel. Therefore, it is urgent to implement an arrangement taking into account the different types of water points of the Ferlo zone.